1986
DOI: 10.3109/02713688608995172
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na, K-ATPase by sodium selenite and reversal by glutathione

Abstract: Sodium selenite has been shown to inhibit Na,K-ATPase. Glutathione, at sufficient excess, is able to prevent or reverse the inhibition. Dithiothreitol can also reverse much of the inhibition, but KCN cannot. Selenomethionine does not inhibit Na,K-ATPase. The interactions of sodium selenite with Na,K-ATPase and glutathione may aid in understanding the early events in selenium cataractogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Resveratrol possibly protects against inhibition of Na + -K + -ATPase and Na + /Ca +2 exchange by detoxification of reactive oxygen radicals. 37,38 In our study, mean lens TN levels in group 2 and group 3 were significantly higher than in group 1 (p < 0.05). In addition, mean TN levels in group 3 were significantly higher than in group 2 (p < 0.05).…”
Section: Discussioncontrasting
confidence: 66%
“…Resveratrol possibly protects against inhibition of Na + -K + -ATPase and Na + /Ca +2 exchange by detoxification of reactive oxygen radicals. 37,38 In our study, mean lens TN levels in group 2 and group 3 were significantly higher than in group 1 (p < 0.05). In addition, mean TN levels in group 3 were significantly higher than in group 2 (p < 0.05).…”
Section: Discussioncontrasting
confidence: 66%
“…Possibly, GSPE may be preventing inhibition of the Ca-ATPase pump and selective calcium permeability by means of scavenging reactive oxygen radicals. 26,27 In a recent study, proanthocyanidins derived from cacao (CLP) were tested for their preventive effect on cataract development in rats with diabetes induced by streptozotocin. 28 The authors found that dietary supplementation with CLP did not affect hyperglycemia but made a significant change in production of hydroxynonenal, a marker of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins, NF-κB, AP-1, caspase-3, Cdk2, protein kinase C and JNK are known to act as redox-dependent signal molecules (35,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Therefore, deregulation of target molecules by selenium-induced thiol modification may be involved in disrupting various signal transduction pathways that control cell survival and apoptosis.…”
Section: Selenium-induced Thiol Oxidation and Ros Generationmentioning
confidence: 99%